The strange case of the alchemist's daughter [compact disc, unabridged] - Goss, Theodora (Simon & Schuster Audio, 2017)
Based on some of literature's horror and science fiction classics, this is the story of a remarkable group of women who come together to solve the mystery of a series of gruesome murders, and the bigger mystery of their own origins.